Make a web-based management management application - Ardiamsah; Jimmie (International Journal Cister, 2022)
Thesis is a scientific work that must be written by undergraduate students as part of the final requirements for academic education. Muhammadiyah University of Palembang is one of the universities in Palembang that educates its students to obtain a bachelor's degree. This study aims to develop a web-based online thesis system using the Waterfall method through the analysis, design and testing stages. This online thesis uses the PHP language with the Codeigniter and Mysql Framework. With the creation of this system, it can make it easier for students and universities in making thesis.